2022
DOI: 10.20473/bikk.v34.2.2022.86-91
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Cure Profile of Tinea Capitis Patients

Abstract: Background: Tinea capitis (TC) is a superficial mycoses infection of hair follicles and hair shaft caused by dermatophytes of the genus Trichophyton and Microsporum. Tinea capitis can cause hair loss and scales with varying degrees of inflammatory response. The incidence varies depending on geographical location and factors that affect the incidence rate. It is important to know the incidence also the clinical and cure profile of tinea capitis to provide benefits in the prevention, diagnosis, and treatment. Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…2 There is still a lack of knowledge on the pathogenesis of post-traumatic headache (PTHA); several hypotheses include altered neurometabolic processes, poor descending regulation, and trigeminal sensory system activation with the probability of several overlapping pathways. 6 Schwedt et al showed that patients with PTHA had structural variations in cortical thickness and brain volume. 14 Diffuse axonal damage after a brain injury may lead to structural remodeling of cortical and subcortical areas in the somatosensory and insular cortex, downregulating the neuromodulation of pain-modulating pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 There is still a lack of knowledge on the pathogenesis of post-traumatic headache (PTHA); several hypotheses include altered neurometabolic processes, poor descending regulation, and trigeminal sensory system activation with the probability of several overlapping pathways. 6 Schwedt et al showed that patients with PTHA had structural variations in cortical thickness and brain volume. 14 Diffuse axonal damage after a brain injury may lead to structural remodeling of cortical and subcortical areas in the somatosensory and insular cortex, downregulating the neuromodulation of pain-modulating pathways.…”
Section: Discussionmentioning
confidence: 99%
“…4 Walaupun tidak mengacam nyawa, penderita tinea kapitis biasanya mengeluhkan gangguan penampilan, dan tidak jarang menyebabkan gangguan psikososial, karena sering dihina, dikucilkan, bahkan diintimidasi oleh teman bermainnya. 5 Noviannisa, et al, (Surabaya, 2020-2021) mendapatkan 10 penderita tinea kapitis yang semuanya merupakan anak-anak usia 0-11 tahun, 6 sejalan dengan penelitian Siregar (Sumatera Utara 2014-2017) yang mendapatkan 32,4% penderita tinea kapitis atau sebanyak 12 orang berusia 1-10 tahun. 7 Yadav VC, et al, di Chhattisgarh (India, 2016) mendapatkan 36% penderita berusia 0-7 tahun.…”
Section: Discussionunclassified